2022
DOI: 10.1371/journal.pone.0264292
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydia trachomatis inclusion membrane protein CT006 associates with lipid droplets in eukaryotic cells

Abstract: Chlamydia trachomatis causes genital and ocular infections in humans. This bacterial pathogen multiplies exclusively within host cells in a characteristic vacuole (inclusion) and delivers proteins such as inclusion membrane proteins (Incs) into the host cell. Here, we identified CT006 as a novel C. trachomatis protein that when expressed ectopically eukaryotic cells can associate with lipid droplets (LDs). A screen using Saccharomyces cerevisiae identified two Incs causing vacuolar protein sorting defects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…To date, seven Inc subtypes (A–G), as well as a newly recognized subtype, Inc V, have been described [ 75 ]. Taking into consideration differences in nomenclature, it should be mentioned that inclusion membrane proteins are characterized by at least one bi-lobed hydrophobic motif; therefore, the in silico prediction is based on the bi-lobed hydrophobic domains occurring in these proteins [ 76 , 77 ]. In this study, four subtypes were identified by a BLAST search: Inc A (two proteins), Inc B (one protein), Inc C (one protein), and Inc V (one protein).…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven Inc subtypes (A–G), as well as a newly recognized subtype, Inc V, have been described [ 75 ]. Taking into consideration differences in nomenclature, it should be mentioned that inclusion membrane proteins are characterized by at least one bi-lobed hydrophobic motif; therefore, the in silico prediction is based on the bi-lobed hydrophobic domains occurring in these proteins [ 76 , 77 ]. In this study, four subtypes were identified by a BLAST search: Inc A (two proteins), Inc B (one protein), Inc C (one protein), and Inc V (one protein).…”
Section: Discussionmentioning
confidence: 99%
“…Some T3SS‐translocated effectors termed inclusion membrane (Inc) proteins are embedded in the inclusion membrane and play a role in the direct interaction of the inclusion membrane with the ER (Bugalhao & Mota, 2019; Derré, 2017; Dumoux et al, 2015). The C. trachomatis Inc protein CT006 associates with LDs and the ER when expressed ectopically in yeast and mammalian cells, suggesting that the protein might participate in the interaction of LDs with the inclusion (Bugalhao et al, 2022).…”
Section: Lipid Droplets Are Transported Into the Chlamydia Inclusionmentioning
confidence: 99%